Solve the factored quadratic equation 0 = -1/3 x * (x - 6)

1 answer

To solve the factored quadratic equation \( 0 = -\frac{1}{3} x (x - 6) \), we can set each factor equal to zero.

  1. The first factor is \( -\frac{1}{3} x = 0 \): \[ x = 0 \]

  2. The second factor is \( x - 6 = 0 \): \[ x = 6 \]

Therefore, the solutions to the equation are: \[ x = 0 \quad \text{and} \quad x = 6 \]

Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
  1. 1)What method(s) would you choose to solve the equation:x2 + 2x - 6 = 0 A. Square roots; there is no x-term. B. Quadratic
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions